Desain Sistem Aplikasi Pelaporan Pelanggaran di Destinasi Pariwisata Prioritas Indonesia Berbasis Prinsip Keberlanjutan - Adamy, Zulham; Wiradharma, Gunawan; Prasetyo, Mario Aditya; Igiriza, Miftahunnisa’; Anam, Khaerul (Universitas Medan Area, 2026)
Amid growing demands for transparency and public participation in tourism governance, public reporting technology is still rarely positioned as a strategic instrument for citizen participation in sustainable tourism destinations. This study aims to analyze the needs and design a complaint reporting system for violations in Indonesia's priority tourism destinations by integrating sustainability principles and RAD approach. Using in-depth interviews with tourism experts and application developers, questionnaires, and field observations in super-priority destinations. The results show that the limitations of manual complaint systems not only hamper the effectiveness of follow-up violations but also weaken the participation of tourists as actors in destination governance. The main findings indicate that a responsive, secure, and transparent digital reporting system has the potential to strengthen the practice of co-production of public services and increase the accountability of tourism destination management. The scientific contribution of this research lies in the expansion of the RAD model's application in the context of participatory technology in the tourism sector, while enriching the e-governance discourse by positioning complaint applications as a medium for tourists and destination managers. This research emphasizes that public reporting technology is strategic instrument in building participatory, ethical, and sustainable tourism destination governance.